Relação entre o uso de "mídias eletrônicas" e os hábitos de sono, sonolência diurna e processos cognitivos em adolescentes - Oliveira, Maria Luiza Cruz de (2016)
The phase delay with respect to schedules of bedtime and wake up time in adolescence added to the growing media use can cause exposure to light at inappropriate times, irregularity of sleep schedules and sleep deprivation, as well as influence the basic cognitive processes, which modulate the performance of the individuals, such as attention, working memory and cognitive flexibility. This context can lead to reduced cognitive performance, impairing learning. In this work, we examine if the sleep habits, daytime sleepiness and cognition in adolescent attending to school at morning shifts vary in function of the media usage. Thus, 83 (60 girls, 23 boys) second grade high school students of private schools in Natal/RN answered questionnaires (Health and Sleep, Horne and Östberg’s Morningness-Eveningness Questionaire and Epworth Sleepiness Scale) and a battery cognitive tests (evaluation of attention by a continuous performance task, working memory, the subtest of digits, and cognitive flexibility for trail making and Berg’s card sorting test). In addition, they completed the sleep diary for 10 days and daily media use log for two weekdays and two weekend days. Overall, media usage was higher in the weekend compared to the weekdays, and the most widely used device is the mobile phone, followed by television and computer. There were no correlations between the estimated weekly use of media and the parameters related to sleep. However, weak correlations were found between the weekly estimate and use: the overall stability in attention (r = -0.23; p <0.05), points (r = 0.22; p <0.05) and total score (r = 0.22; p <0.05) in the direct order of the digit subtest, and the isolated errors (r = -0.26; p <0.01) on Berg’s test. Concerning frequency of media use before bed, television appears as the preferred device for the group that have the higher frequency media use before bed (G3). The schedules of bedtime, wake up time and time in bed, in general, differ between weekdays and weekend (ANOVA, p<0,05). Overall, the G1 individuals have sleep patterns with more advanced times when compared to adolescents from others groups. G1 differ from others groups in wake up time in the weekend (ANOVA, p<0,05) and from G3 in time in bed on week (ANOVA, p<0,05 – Bonferroni, p=0,06). Most students had excessive daytime sleepiness, with differences in proportions between groups. However, the highest percentages were observed successively in G1 and G3 (X², p <0.05). For performance on cognitive tests, the G1 had a lower percentage of omissions in phasic alert (Mann-Whitney test, p <0.05), a tendency to a lower percentage of omissions in relation to the sustained attention (Kruskal-Wallis, p = 0 , 06), most points in the indirect order of the digit subtest (Mann-Whitney test, p <0.05) and greater efficiency in version A of the trail making test (Mann-Whitney test, p <0.05 ). Overall, these results support our hypothesis that the media use affects sleep, daytime sleepiness and cognitive performance, especially when the use of electronic devices occurs near the bedtime schedules. However, further studies with a larger number of individuals is required to confirm this evidence.